Inside a High - Speed Train - Uttley, Colin (Danbury, CT Grolier Publishing, 2001)
Each book in this series gives the reader the history behind its subject, the working machinery as well as a glimpse into the future.
5 - 9
Keywords: Electric railroad; Railroads